2013
DOI: 10.5424/fs/2013222-03553
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dynamics of Quercus ilex advance regeneration in a Pinus nigra plantation after the creation of small canopy gaps

Abstract: Aim of the study: The aim of the research is to analyse the role of Quercus ilex advance regeneration in the stand regeneration of pine plantations after small-sized canopy openings, and to assess the influence of the forest stand and the canopy opening. The performance of the advance regeneration under the pine plantation is also examined.Area of study: A Pinus nigra plantation in dry Continental Mediterranean climate in eastern Spain. Material and methods:The tree regeneration of ten canopy openings of 0.17-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…3). The natural establishment rate we recorded in 2014 (54.2 seedlings ha -1 ) is lower than those we estimated from data reported by Pulido and Díaz (2005) in oak woodland (123 seedlings ha -1 year -1 ) and by García-Barreda and Reyna (2013) in gaps of a planted pine forest (120 seedlings ha -1 year -1 ), but higher than that found by Pulido and Díaz (2005) in an oak savanna (2.8 seedlings ha -1 year -1 ). Gómez et al (2003) also found that 98 % of the 1000 experimental seedlings were killed by herbivores, notably wood mice, wild boar, and domestic and wild ungulates.…”
contrasting
confidence: 52%
“…3). The natural establishment rate we recorded in 2014 (54.2 seedlings ha -1 ) is lower than those we estimated from data reported by Pulido and Díaz (2005) in oak woodland (123 seedlings ha -1 year -1 ) and by García-Barreda and Reyna (2013) in gaps of a planted pine forest (120 seedlings ha -1 year -1 ), but higher than that found by Pulido and Díaz (2005) in an oak savanna (2.8 seedlings ha -1 year -1 ). Gómez et al (2003) also found that 98 % of the 1000 experimental seedlings were killed by herbivores, notably wood mice, wild boar, and domestic and wild ungulates.…”
contrasting
confidence: 52%
“…canopy openness). Under shade conditions, the established Q. ilex are nevertheless able to persist without significant net growth (Espelta et al, 1995;Garcia-Barreda and Reyna, 2013), forming dense seedling banks and perpetuating through repeated shoot dieback and re-sprout until light conditions improve (Johnson et al, 2009). …”
Section: Tablementioning
confidence: 98%
“…), the characteristics of the stand (over-and understory structure and composition) and the attributes of the canopy layer (gap shape, size) (e.g. Lookingbill and Zavala, 2000;Smit et al, 2008;Garcia-Barreda and Reyna, 2013).…”
Section: Introductionmentioning
confidence: 99%